The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/cells9040946
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Tufting Enteropathy-Associated Mutant of Epithelial Cell Adhesion Molecule Activates the Unfolded Protein Response in a Murine Model of the Disease

Abstract: Congenital tufting enteropathy (CTE) is a rare chronic diarrheal disease of infancy caused by mutations in epithelial cell adhesion molecule (EpCAM). Previously, a murine CTE model showed mis-localization of EpCAM away from the basolateral cell surface in the intestine. Here we demonstrate that mutant EpCAM accumulated in the endoplasmic reticulum (ER) where it co-localized with ER chaperone, GRP78/BiP, revealing potential involvement of ER stress-induced unfolded protein response (UPR) pathway in CTE. To inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…ER stress is also reported to be responsible for loss of intestinal epithelial stemness [40] through activation of the unfolded protein response (UPR). Our prior finding of ER stress and UPR in CTE mice [41] may be the cause of of the loss of Lgr5-positive ISCs in these mice. Further studies are needed to explain the direct mechanism by which mutant EpCAM affects Lgr5-positive ISCs but not other stem cells, transient amplifying cells or other progenitor cells.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…ER stress is also reported to be responsible for loss of intestinal epithelial stemness [40] through activation of the unfolded protein response (UPR). Our prior finding of ER stress and UPR in CTE mice [41] may be the cause of of the loss of Lgr5-positive ISCs in these mice. Further studies are needed to explain the direct mechanism by which mutant EpCAM affects Lgr5-positive ISCs but not other stem cells, transient amplifying cells or other progenitor cells.…”
Section: Discussionmentioning
confidence: 69%
“…Thus, the observation that NHE3 protein, but not at mRNA, expression may imply post transcriptional regulation via altered interactions with the PDZ domain protein, NHERF [43]. Moreover, we recently reported that endoplasmic reticulum stress and the unfolded protein response (UPR) play a role in pathogenesis in mutant EPCAM mice [41]. Activation of UPR might lead to alterations in polarized absorptive enterocytes, which normally depend on intracellular transport of various components of the brush border for proper functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant EpCAM (deletion of exon 4) is not present on the cell surface, it rather accumulates in the ER. This activates the ER stress-induced mechanism unfolded protein response (UPR) [ 96 ]. There are also two reports of homozygous full EPCAM gene knockouts [ 80 , 87 ]; however, they are lethal in mice [ 97 ].…”
Section: Epcam Structure and Diseasesmentioning
confidence: 99%
“…However, the connection between structural and functional consequences of mutations is not immediately obvious in case of extracellular single amino acid substitutions, far from the identified interaction surfaces with the abovementioned proteins (for an extensive review please see [ 83 ]). We hypothesize that these mutations affect the stability of EpCAM protein as a whole and lead to either its increased internalization or proteolytic degradation or accumulation in ER, as in the case of exon 4 deletion mutant [ 96 ].…”
Section: Epcam Structure and Diseasesmentioning
confidence: 99%